Assessing the Impact of Alternative Fair Value Measures on the Efficiency of Project Selection and Continuation - Caskey, Judson; Hughes, John S. (The Accounting Review, 2012)
ABSTRACT We examine how alternative accounting measures of fair value impact the ability of debt covenants to mitigate inefficient investment decisions. In our setting, shareholders make a non-contractible project choice after signing a debt contract. At a later date, the project can be abandoned and new information determines whether shareholders or creditors make that decision. The value of debt covenants depends on their ability to deter costly asset substitution while also mitigating inefficient continuation decisions. A covenant based on a conservative fair value measure tends to perform best in this respect. Departing from purely fair-value-based covenants, an even more conservative covenant based on fair values and historical cost outperforms those based solely on fair values. Notably, the “highest and best use” measure advocated by the FASB performs poorly in deterring the choice of inferior projects. Our results provide a setting in which the contracting efficiencies associated with different accounting measures cannot be replicated across measures by altering covenant “triggers.”